Elektronik Belge Yönetim Sistemi (EBYS) Uygulamalarında Başarı Faktörü ve Fayda Analizi - (:unkn) unknown (My University, 2016)
Bu çalışmanın amacı, organizasyonların Elektronik Belge Yönetim Sistemi (EBYS) uygulamalarında başarı sağlamalarına yönelik faktörleri ve EBYS'nin organizasyonlara sağlayacağı faydaları analiz etmektir. Bu makalenin tasarımı alan uygulamasından edinilen tecrübeler ve literatür ışığında geliştirilmiştir. EBYS uygulamasındaki başarı faktörleri çeşitli kategoriler altında incelenmiştir. EBYS için sistem ve belge ilkeleri temel olarak ele alınmış, EBYS uygulamasında sürdürülebilirlik ve pilot uygulama süreçlerine vurgu yapılmıştır. Bu çalışma daha çok bir araştırma makalesidir ve organizasyonlara yol gösterecek bazı pratik ilke ve özellikleri vurgulamaktadır.Edinilen bulgular; organizasyonların EBYS'yi sistem ve belge yönetimi ile iyi anlaması ve yatırımlarını planlı şekilde bir proje üzerinden yapması gerekliliğidir. Başarı faktörüne ulaştıran etkenler, risk yönetimi, personel yönetimi, değişim yönetimi, kalite ve teknoloji yönetimi, proje yönetimi, kapasite geliştirme, politika ve çerçeve oluşturma ve iş belge analiz süreçleri olarak teker teker ele alınmıştır. Bununla beraber EBYS'nin faydası organizasyonlar, çalışanlar, toplum, finansal ve çevresel açıdan yüzeysel olarak incelenmiştir.Bu çalışma EBYS ile ilgili başarı faktörü kavramını incelemesi ve ilgililere yol gösterici bir özellikte olması açısından önemlidir.

The aim of this study is analyse the factors that contribute to the successful implementation of ERMS by organisations and the benefits gained through ERMS implementation. The scope of this article was developed through experience gained through fieldwork and a review of scholarly literature. The factors that contribute to the successful implementation of ERMS have been examined under various categories. An examination of ERMS was based upon system and records principles whereas the processes of the pilot implementation and maintainability was stressed in ERMS implementation.This study is more of a research article and is written with the aim of stressing practical principles and characteristics that will act as a guide for organisations. Findings show that organisations should have a good understanding of ERMS as a system and records management and that investment in ERMS should be realised through a planned project. Factors that ensure success such as risk management, staff management, change management, quality and technology assurance, project management, capacity development, formation of policy and framework and business records analysis processes, have individially been addressed. The benefits of ERMS which can be categorised in the following categories were also examined albeit in a less detailed manner; organisations, staff, society, financial and environmental. In addition, organisations should bear in mind these progress factors during the decision making process of ERMS implementation and the off the shelf or bespoke ERMS application should be evaluated in accordance with these success principles. This study is important in that it examines the progress factor in relation to ERMS and acts as a guide to those involved in the process.
Progress Factors and Benefit Analysis in Electronic Records Management System (ERMS) Implementation